Ubr1p-Cup9p-Ptr2p pathway involves in the sensitivity to readthrough compounds negamycin derivatives in budding yeast. Issue 10 (3rd October 2019) - Hamada, Keisuke; Naito, Akari; Hamaguchi, Yu; Kanesaki, Yu; Kasahara, Koji; Taguchi, Akihiro; Omura, Noriko; Hayashi, Yoshio; Usui, Takeo
ABSTRACT: In this study, we found that dipeptide transporter Ptr2p is the putative transporter of read-through compounds (+)-negamycin derivatives TCP-126 and TCP-112, in budding yeast. Ptr2p expression and activity were correlated with the TCP-112 sensitivity, and dipeptide with high affinity to Ptr2p suppressed the TCP-112 activity. These results suggest that dipeptide transporter is one of the determinants of negamycin analogs sensitivity. Abbreviation : PTC: premature termination codon.